Analysis of The Wife of Bath’s Tale from Geoffrey Chaucer’s Canterbury Tales through the Lense of Propp’s Narrative Function - Marko Lim Aratea (Universitas Sanata Dharma, 2025)
This study examines Geoffrey Chaucer's The Wife of Bath's Tale through Vladimir Propp's narrative functions as a means of understanding how Chaucer follows and subverts traditional structures of folktales. The Canterbury Tales is one of the most important works in medieval literature, while The Wife of Bath's Tale is especially famous for its complex depiction of gender relations, power, and moral teaching. The purpose of the investigation is to explain the structural elements of the tale using Propp's 31 narrative functions applied to folk stories. In mapping these functions onto the tale, the research underlines how Chaucer follows conventional patterns of storytelling but innovates in crucial areas, mainly when it comes to gender roles and moral redemption. This study used a structuralist approach which examines exactly how this knightly quest of redemption was non-traditional in that his intellectual and moral growth was pitted against the more physical challenges of traditional narratives. The results of the analysis are that 18 of Propp's functions are represented, whereas several of the most important functions—struggle and victory among them—are negated. Through this, Chaucer attacks the gendered prescription of medieval society and, through the figures of the queen and the old woman, develops firm arguments for female self-determination. The study concluded that Chaucer draws upon Propp's narrative structure in his resistance to and rearticulation of socially held attitudes regarding gender, power, and heroism—to develop the tale into a progressivist critique against traditional medieval values.